MORPHOMETRICAL STUDY FOR DEVELOPMENT OF VOMER BONE IN INDIGENOUS SHEEP FETUSES - Saffana Kh.M.J.Al-Taee (Basrah Journal of Veterinary Research)
This study included detection the onset time of ossification of vomer bone in indigenous sheep fetuses collected from uteri of indigenous ewes slaughtered in Mosul city, which prepared by using modify double staining method in younger age or maceration with potassium hydroxide (KOH) or with fly larvae in old ages. The first sign of vomer bone demonstrated as a small areas (3mm) in the (53) days old of indigenous sheep fetus as a two bilateral ossification centers which located below and above the vomeral body which formed by intramembranous ossification in the membrane covering the cartilaginous nasal capsule. The results revealed that the relative increase in the vomer bone during thirteen successive weeks [8th – 20th weeks]of indigenous sheep fetal age, that the greatest relative increase in vomer bone length was at the 8th week, while the greatest relative increase in vomer bone height was in the 11th week of indigenous sheep fetal age.